Structural recurrence in well-differentiated papillary thyroid carcinoma: a 10-year single center cohort study - Dias, Francisco Araújo; Souza, Rafael Pereira de; Briaunys Milan, Tabata; De Cicco, Rafael (Oncology Reviews, 2025)
IntroductionWell-differentiated papillary thyroid carcinoma (PTC) generally carries an excellent prognosis; however, certain pathological features such as gross extrathyroidal extension and tumor diameter ≥2 cm have been associated with structural disease recurrence. This study aimed to identify the key clinical and histopathological factors associated with disease-free survival in patients undergoing total thyroidectomy for PTC.MethodsA retrospective cohort study was conducted including 750 patients who underwent total thyroidectomy with or without neck dissection between 2014 and 2024 at a tertiary academic cancer center. Clinical, pathological, and oncological follow-up data were analyzed over a maximum follow-up period of 100 months. Kaplan–Meier survival analysis, log-rank testing, and Cox proportional hazards regression were employed for statistical evaluation.ResultsThe structural recurrence rate was 4%, and overall survival reached 99%. In the multivariate analysis, only gross extrathyroidal extension (HR 3.29; p = 0.008) and tumor diameter (HR 1.32; p = 0.013) were independently associated with recurrence. Variables such as age, smoking status, perineural invasion, vascular invasion, and central lymph node involvement did not show significant associations with structural recurrence.ConclusionGross extrathyroidal extension and increased tumor diameter were identified as the primary prognostic factors for structural recurrence in patients with PTC. Multicenter studies are warranted to validate these findings in the broader Brazilian population.